Urgency and Adaptation of New Literations in Primary School Education in the Digital Era - Desvian Bandarsyah (AL-ISHLAH: Jurnal Pendidikan, 2021)
Teachers have been aware of the urgency of literacy; however, some teachers are still neglected. The main purpose of this paper is to discuss new literacy in the digital era, which includes primary school education. Our primary education is an important actor in preparing Indonesian future generations. The research method used was a literature review to view the diversity of culture and awareness among Indonesian. Data had been collected throughout history recorded in digital, books, and many others. Data were analyzed using comparing the diverse history related to primary education. By comparing data, we make a framework that is used to organize future primary education. The results show that the digital era and literacy are becoming integrated to improve learning and teaching quality. Both teachers and students should be aware a digital literacy should improve the quality of our education. The study's implications will be used to assess how effective literacy education has improved educational quality.